A Generalized Network with Material Routing for Mineral Supply Analysis - D. J. Shields (The Southern African Institute of Mining and Metallurgy, 1987)
The U.S. Bureau of Mines has developed a microcomputer-based mineral modelling system that enhances analytical capabilities of the agency. It draws upon the extensive data base previously developed for the Bureau's Availability studies. The model is first formulated as a generalized network flow optimization problem, the optimal flows from which are fed into a transportation algorithm. The goal of the modelling system is first to fulfill prespecified demand at the minimum opportunity cost and second to identify feasible, optimal trade patterns. The system facilitates the analysis of policy issues on a real-time basis and supports the Bureau's mission to assess mineral resources.